Kuliah Kerja Nyata Terpadu CSR Perusahaan Konstruksi Bagi Masyarakat - deden, deden (Humanis, 2023)
Real Work Lectures (KKN) is a form of community service carried out by students in an interdisciplinary, institutional and partnership manner as a form of higher education tridharma activities. As the social dynamics of society, regional government, central government and the global world change, the KKN program at Gunung Jati Swadaya University (UGJ) is directed at a KKN pattern based on community empowerment. CSR (Corporate Social Responsibility) has been popularly used in Indonesia since the 1990s. Several companies have actually been carrying out CSA (Corporate Social Activity) or "corporate social activities" for a long time. Even though we don't call it CSR, in fact the action is close to CSR, which represents a form of company "participation" and "concern" for social and environmental aspects. The method for implementing CSR integrated KKN is academics (students and lecturers) through KKN activities in collaboration with PT. PP (Persero) is actively involved in implementing CSR activities. The CSR method used by PT. PP (Persero) in the construction sector, especially in the field of road and bridge construction, is by direct involvement and establishing partnerships, where in this method the company directly enters into partnerships with stakeholders and the community, carrying out CSR directly to communities in need. The result of implementing CSR is that the company contributes assist the government in economic development, poverty alleviation, and the like. CSR also provides benefits for the company itself. With CSR, the company will be closer to the surrounding community while getting operational support, and the company will also get a good and positive image in the eyes of the community. Apart from that, CSR can help society in various fields, for example the economic sector such as distributing basic necessities, compensation, and so on. There are also in the health sector such as blood donation programs, Covid-19 vaccinations, and so on.